1176. Quality of Life of Previously Healthy Subjects following Cryptococcal Meningoencephalitis. (31st December 2020) - Dean, Owen; Anjum, Seher; Scott, Terri; Ham, Lillian; Powers, John H; Snow, Joseph; Williamson, Peter
Abstract: Background: Cryptococcal meningoencephalitis (CM) causes significant morbidity and mortality in HIV-negative, previously healthy populations. This group has significant disease sequalae including a fronto-subcortical syndrome, hearing loss, vision loss, and spinal arachnoiditis. However, the health-related quality of life (HRQOL) of this group of patients following microbial recovery from infection has not been reported. Methods: We cross-sectionally defined the HRQOL of previously healthy individuals with CM seen at the NIH Clinical Center since 2013 and at least one year past diagnosis using the Quality of Life in Neurological Disorders (Neuro-QoL) project short forms. These forms assess domains such as anxiety, fatigue, depression, dexterity and mobility in patients with chronic neurological disease. Form scores were calculated for each domain and centered to a general or clinical United States population reference. Impairment was considered a subject score of least one half a standard deviation (SD) lower than the population reference average. Results: Of 43 subjects with CM (mean age 48 years, 56% male, mean time from diagnosis 5.7 years), 91% had evidence of impairment in at least one HRQOL domain. Notable findings included self-reported impaired cognitive function in 53% and sleep disturbance in 56%. Impaired satisfaction with social roles and activities was present in 44%. Mobility and dexterity were impaired in 30% respectively. The number of impaired HRQOL domains was not significantly different in subjects with a history of neurosurgical intervention during hospitalization (mean no. impaired domains 4.4 vs. 3.3, P=0.43) or methylprednisolone treatment for post-infectious inflammatory response syndrome (4.3 vs. 3.4, P=0.63). Cerebrospinal fluid glucose levels on admission were negatively correlated with the number of impaired functional domains (rs =-0.33, P=0.05, n=38). Patient reported quality of life domains following microbial recovery from cryptococcal meningoencephalitis. Box plots show median, 25th, and 75th percentiles.The gray dotted line represents the mean T-score (50) of the U.S. population reference for each Neuro-QoL domain. The yellow region designates mild symptoms or impairment (0.5-1.0 std below the population mean), orange, moderate (1.0-2.0), and red, severe (2.0-3.0). The asterisk* indicates measures that were centered to U.S. clinical reference population. All other domains were centered to a U.S. general population reference. Abbreviations: CNS, central nervous system, U.S., United States, ADL, activities of daily living, SRA, social roles and activities Conclusion: This is the first report of HRQOL deficits in previously healthy individuals following microbial recovery from CM. These data reinforce and quantify the long-term morbidity of this disease and identify patient-centered outcomes for future interventional trials. Disclosures: All Authors : No reported disclosures